2021
DOI: 10.1093/ehjacc/zuab040
|View full text |Cite
|
Sign up to set email alerts
|

Classification performance of clinical risk scoring in suspected acute coronary syndrome beyond a rule-out troponin profile

Abstract: Aims High-sensitivity cardiac troponin strategies can provide risk stratification in patients with suspected acute coronary syndrome (ACS) in the emergency department (ED). This study evaluated whether clinical risk scoring improves the classification performance of a rule-out profile in suspected ACS. Methods and results Patients presenting to ED with suspected ACS as part of the RAPID-TnT trial randomized to the interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A recent analysis of the the Rapid Assessment of Possible Acute Coronary Syndrome in the Emergency Department with High-Sensitivity Troponin T Study (RAPID-TnT) study found no improvement in classification performance in adding the HEART score to ruled-in patients in terms of identifying 30-day death or MI. 24 The present study differs from RAPID-TnT in that the HEART score was applied to a cohort of patients with chest pain who ruled-in but whom clinicians felt were candidates for discharge based on factors beyond the ADP result, and this difference may explain the additive value of the HEART score in this study.…”
Section: Jama Network Open | Cardiologymentioning
confidence: 96%
“…A recent analysis of the the Rapid Assessment of Possible Acute Coronary Syndrome in the Emergency Department with High-Sensitivity Troponin T Study (RAPID-TnT) study found no improvement in classification performance in adding the HEART score to ruled-in patients in terms of identifying 30-day death or MI. 24 The present study differs from RAPID-TnT in that the HEART score was applied to a cohort of patients with chest pain who ruled-in but whom clinicians felt were candidates for discharge based on factors beyond the ADP result, and this difference may explain the additive value of the HEART score in this study.…”
Section: Jama Network Open | Cardiologymentioning
confidence: 96%
“…While such models are useful in some circumstances, they may be less useful at a patient level, where exclusion of a single condition does not provide a diagnosis or estimation of overall patient risk. The HEART, EDACS and TIMI risk scores stratify chest pain patients according to risk of ACS or subsequent MI, and the discriminatory metrics of these scores may relate to differentiating ACS from other serious conditions that require treatment [5] , [9] , [10] , [11] . Moreover, these scores were developed in the conventional troponin era and while each have been validated with high-sensitivity troponin assays, they may offer more limited benefits in the setting of newer rapid rule-out pathways [5] , [6] .…”
Section: Discussionmentioning
confidence: 99%
“…The HEART, EDACS and TIMI risk scores stratify chest pain patients according to risk of ACS or subsequent MI, and the discriminatory metrics of these scores may relate to differentiating ACS from other serious conditions that require treatment [5] , [9] , [10] , [11] . Moreover, these scores were developed in the conventional troponin era and while each have been validated with high-sensitivity troponin assays, they may offer more limited benefits in the setting of newer rapid rule-out pathways [5] , [6] . Existing scores and rapid troponin pathways do not provide information regarding the risk of a non-coronary diagnosis being present, which partially limits their utility in facilitating early discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation